Problems of harmful habits and dependences of students. - Gorobey Nikolaj Petrovich (Kharkov National Pedagogical University, 2011)
The analysis of data of modern scientific literature is conducted on issue of harmful habits and dependences of students. It is shown that considerable part of student young people have harmful habits and dependences. Negative influence of harmful habits and dependences of students is exposed on the state of their health. Importance of delivering is well-proven from addiction behavior in practice of healthy way of life of students. It is set that one of foreground jobs of present time there is an increase of level of education of student young people on questions abandonment from harmful habits and dependences. The ways of decision of problem of addiction behavior of students are offered as an effective condition of improvement of the state of their health.